For a), I got the answer as -2x^2^-2 +5x^-2. Is this correct? And as for part b), I don't know how to do it. Please help, thanks,
First, simplify it to
x-5 - 24/x
x-5- x^-1 (24) now take the derivative
1+24 (x^-2) re-arrange
it is the derivative of [ x^2-5x-24] / x Note the red part.....
I turned x into x-1 which differentiates to -x-2 which I then multiplied by the numerators (2x and -5). Is that wrong?
It's x-1 (x2-5x-24) <===== take the derivative of THIS ( you see there is a term 24x-1 you cannot discard this portion )
Look at the graph.....what do you think?
Well it's a tangent to the original equation, so I think that it's definitely correct.